Up or out: Research incentives and career prospects of postdocs in Germany - Bernd Fitzenberger; Ute Leuschner (Institute for the Study of Labor (IZA), 2012)
Academic careers in Germany have been under debate for a while. We conduct a survey among postdocs in Germany, to analyze the perceptions and attitudes of postdocs regarding their research incentives, their working conditions, and their career prospects. We conceptualize the career prospects of a postdoc in a life-cycle perspective of transitions from academic training to academic or non-academic jobs. Only about half of the postdocs sees strong incentives for academic research, but there is quite a strong confidence to succeed in an academic career. Furthermore, postdocs who attended a PhD program show better career prospects and higher research incentives compared to others. Academic career prospects and motivation are strongest for assistant professors. Apart from this small group, however, postdocs report only a small impact of the university reforms of the last decade. Female postdocs show significantly higher research incentives but otherwise we find little gender differences. Finally, good prospects in non-academic jobs are not associated with a reduction in the motivation for research.
urn:nbn:de:101:1-201206146927
Keywords: A11; A29; I21; I23; J24; J49; 330; postdocs; academic career prospects; research incentives; university reforms; Wissenschaftler; Akademiker; Erwerbsverlauf; Leistungsanreiz; Forschung; Wahrnehmung; Deutschland